Comparison of AHP and SAW Methods for Predicting Career Interests of SMAN 1 Karanganyar Demak Students - Prabowo, Ardian Adi; Supriyanto, Aji (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study compares the efficacy of the Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods in predicting career interests of students at SMAN 1 Karanganyar Demak. The research assesses seven key factors: familial influence, educational engagement, individual capabilities, academic performance, institutional resources, resilience of a career, and academic interests. Results show that AHP prioritizes familial influence (28.94%), individual capabilities (17.10%), and educational engagement (16.23%), while SAW highlights career (15.75%), educational engagement (15.61%), and individual capabilities (14.92%). Both methods achieved an accuracy of 83.02%. Career recommendations were categorized into guidance-intensive cases (AHP: 42.68%; SAW: 46.00%), employment-oriented individuals (AHP: 33.96%; SAW: 32.97%), higher education aspirants (AHP: 12.94%; SAW: 10.06%), and entrepreneurial prospects (AHP: 10.42%; SAW: 10.96%).